The influence of team reflexivity and shared meta-knowledge on the curvilinear relationship between team diversity and team ambidexterity. Issue 5 (14th May 2018) - Li, Ci-Rong; Li, Chun-Xuan; Lin, Chen-Ju; Liu, Jing
Abstract : Purpose: The purpose of this paper is to explicate the influence of diverse team on team-level ambidexterity and its curvilinear assessment, and test the mediating role of team reflexivity and the moderating role of shared meta-knowledge in the curvilinear relationship between team diversity and team ambidexterity. Design/methodology/approach: The authors collected multisource and temporally separated data on 206 R&D teams within 28 high-tech firms in Taiwan. Findings: This study found a complex, curvilinear, moderated mediation relationship that functional background diversity has with team ambidexterity. Furthermore, consistent with the notion from categorization-elaboration model, the authors found the curvilinear relationship that functional background diversity has with both team ambidexterity and team reflexivity. Finally, the authors also found that the curvilinear relationship between functional background diversity and team reflexivity was moderated by shared meta-knowledge, such that the positive relationship was strengthened and the negative relationship weakened, in higher shared meta-knowledge in teams rather than lower. Originality/value: The results demonstrate that team diversity-team ambidexterity relationship is much more complicated than previous works have assumed or suggested. Overall, the authors contribute to a novel understanding about the importance of team diversity in ambidextrous teams by opening the black box of how and when functional background diversity and team ambidexterity.